Comparative Analysis Of The Thoughts Of Fahim Khan And Muhammad Abdul Mannan About The Concept Of Islamic Consumption - Puspitasari, Dini (Universitas Trunojoyo Madura, 2020)
Increasing income at some point, the community has shifted its consumption pattern from food to non-food. This research is in response to the current phenomenon of society as well as problem solving and evaluation of the shift of public consumption patterns into modern consumption patterns due to increasing income.Â The focus of this paper is about the concept of Islamic consumption from the thinking of contemporary figures, namely Fahim Khan and Muhammad Abdul Mannan. The method used is descriptive qualitative with library research and a primary source used from the book Essays in Islamic Economics by Fahim Khan and Islamic Economics; Theory and Practice by Muhammmad Abdul Mannan.Â The results of this study show that the thoughts of Fahim Khan and Muhammad Abdul Mannan have similarities on indicators of Islamic consumption balance, the concept of Islamic needs and the concept of preference in Islamic consumption. And there are differences in surveillance in Islamic consumption, namely on the institutional framework.Â